PENGARUH LITERASI KEUANGAN TERHADAP KINERJA KEUANGAN UMKM DI WILAYAH KASAWARI DAN SEKITARNYA - Christine Monica Saren (AT TARIIZ : Jurnal Ekonomi dan Bisnis Islam, 2025)
This study aims to examine the influence of financial literacy on the financial performance of Micro, Small, and Medium Enterprises (MSMEs) in the Kasawari region and its surroundings. Financial literacy is considered a crucial capability that affects business owners’ financial decision-making, including capital management, budgeting, and investment planning. The research employs a quantitative approach using simple linear regression analysis. The sample consists of 50 MSME actors selected through purposive sampling. The results show that financial literacy has a positive and significant effect on MSME financial performance, with a regression coefficient of 0.68 and a significance value of 0.000. The coefficient of determination (R²) is 0.476, indicating that financial literacy explains 47.6% of the variation in financial performance. These findings reinforce previous studies that emphasize financial education as a strategic tool for local economic empowerment. The study recommends enhancing financial literacy through training and mentoring programs to strengthen MSME competitiveness and sustainability.